The performance of the fiber optic links system / Mohd Nasrin Kasa - Kasa, Mohd Nasrin (2001)
Fiber optic has become the method of choice for telecommunications because of the advantages and ease in which system can be used. Choosing the correct fiber type is one of the most important procedure in designing any optical fibers link system. This project involved in evaluating the performance of the fiber optic cable using a simulation program created using the Visual Basic (VB) software package. The characteristics evaluated include dispersion, attenuation, bandwidth, bit rate and data rate.